The Role of Artificial Intelligence as a Mediator: Previous Psychological Factors and Purchase Intention - Niswatul Faizah; Kunti Sunaryo; Abdul Ghofar (AIBPM Publisher, 2025)
This study aims to analyse the influence of psychological factors namely, subjective norm, attitude and perceived control on purchase intention through artificial intelligence (AI) in the context of e-commerce. The Theory of Planned Behaviour (TPB) and the Technology Acceptance Model (TAM) are used to explain the relationship between these psychological variables and the acceptance of AI technology. Data were analysed using the structural equation modelling-partial least squares (SEM-PLS) method. The results showed that subjective norms and perceived control significantly and positively affected both AI and purchase intention, directly and through AI mediation. However, attitude had no significant effect on AI or purchase intention through AI. These findings make a theoretical contribution by expanding the application of TPB and TAM in the context of AI-based technology, while also providing e-commerce companies with practical insights to enhance user experience through AI-based personalisation